The inducement aspect an autonomous investment on civil building: a review for the Brazilian economy for 2012-2020 period - Dos Santos, Rômulo Bernardo; Kaio Glauber Vital da Costa; Julia de Medeiros Braga (Brazilian Keynesian Review, 2023)
The present work contributes to the scarce empirical and theoretical literature about the civil construction sector from an aggregate perspective. Firstly, a survey of public policies directed to the sector is carried out. The credit impulse for infrastructure works is then calculated and its relationship with the Brazilian economic activity and investments in construction is analyzed. Then, long-term relationships are estimated between the gross fixed capital formation in construction and economic variables. Causalities are also tested based on Toda and Yamamoto (1995), based on monthly data provided by the Central Bank of Brazil and IBGE for the period from 2012 to 2020. The results indicate that investments in civil construction are affected by the concession credit and interest rates for the real estate sector. There is also an accelerating effect, which is boosted by expectations of bigger aggregate demand, as suggested by the Sraffian Supermultiplier approach. We interpret the results as a sign that specific monetary and credit policy measures, in particular, and aggregate demand stimulus, in general, are effective in boosting investments in civil construction.